LONG-TERM CHANGES IN CRUSTAL MOVEMENTS AND DEFORMATIONS BEFORE AND DURING THE 2016 KUMAMOTO EARTHQUAKE SEQUENCE - V. I. Kaftan; V. N. Tatarinov; R. V. Shevchuk (Геодинамика и тектонофизика, 2022)
The Kyushu Island, as well as whole Japanese archipelago, is equipped with dense GPS network (GEONET). It allows us to track the movements and deformations of the earth’s surface over long-term time intervals. In this study, based on daily determinations of the coordinates of GPS stations, analysis has been made on long-term trends in the accumulation of movements and deformations in large areas of the Kyushu Island before the series of April 14–16, 2016 Kumamoto earthquakes to identify deformation precursors and locked, immobile fault zones. The study of the seismic deformation process was performed using the data from 70 continuous permanent GPS stations for the period 2009–2016.The movement and deformation features found characterize the kinematics of the axial zone of the southwestern part of the island arc of the Japanese archipelago. The combination of coseismic compression and uplift in the center of the formed triad of deformation extrema and the consistency between subsidence and extensions at its edges demonstrate the mechanism of growth of the central region of the island arc under compression and the role of volcanism. Of particular interest in the context of the development of movements and deformations during the generation of the Kumamoto earthquakes is the behavior of the minimum displacement moduli of the GNSS sites. Analysis of their kinematics shows the formation of a zone of minimum displacements, in which subsequent strong seismic events were localized. It is shown that rather dense and extensive GNSS networks allow observing and studying the seismic-deformation process at the stages of seismic generation, discharge and relaxation, thereby providing an empirical basis for the development of models for predicting large seismic events.